THEMATIC HADITH STUDIES: Hadiths on Self-Healing and Their Implementation in the Contemporary Era - Fatimah, Siiti; Lisalam, Repa Hudan; Kurniawan, Ade Fakih; Millah, Mus’idul (Al-Bukhari : Jurnal Ilmu Hadis, 2023)
Abstract Self Healing is a healing process carried out by oneself. The process of self-healing refers to the ability of individuals to activate their internal resources to restore their own physical, mental and emotional health. This study aims to show that individuals who have a better understanding of themselves through self-healing based on hadith. The discussion in it explains the application of hadith in the self-healing process. The method used in this study is the hadith thematic method and uses the grounded theory method. Researchers found 16 hadiths about self-healing narrated by Shahih Bukhari, Shahih Muslim, Sunan Tirmidzi, Sunan Ahmad, Sunnan Abu Dawud and Sunnan Darimi. This study concludes that self-healing with hadith is a good step in solving life problems faced by a person, especially in this era where virality is a reference, therefore, implementing self-healing hadiths in the contemporary era is a step the right one to use.